2006
DOI: 10.1063/1.2397687
|View full text |Cite
|
Sign up to set email alerts
|

A time correlation function theory describing static field enhanced third order optical effects at interfaces

Abstract: Sum vibrational frequency spectroscopy, a second order optical process, is interface specific in the dipole approximation. At charged interfaces, there exists a static field, and as a direct consequence, the experimentally detected signal is a combination of enhanced second and static field induced third order contributions. There is significant evidence in the literature of the importance/relative magnitude of this third order contribution, but no previous molecularly detailed approach existed to separately c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Much prior work has demonstrated that sum frequency intensities decrease with decreasing surface potentials either as a result of the decreasing surface field orienting interfacial liquid molecules less strongly, a decreasing χ (3) contribution to the sum frequency signal or both. McLoughlin et al have shown that adsorption of DNA to the cationic lipid DODAB (dioctadecyldimethylammonium bromide) leads to a decrease in surface potential of ≈0.3 V while adsorption of DNA to the zwitterionic lipid DSPC (distearoyl- sn -glycero-3-phosphocholine) in the presence of Ca 2+ (the change in surface potential for the bare DSPC monolayer in the presence of DNA was not measured) leads to a decrease in surface potential of less than 0.1 V. If we assume that DPTAP and diC14-amidine behave similarly to DODAB and DPPC similarly to DSPC, the change in spectral response with DNA adsorption appears to map qualitatively to the potential decrease: DNA adsorbed to a cationic lipid leads to a larger surface potential decrease than that adsorbed to a zwitterionic and the former system shows a larger decrease in hydrogen bonded OH stretch intensity than the latter.…”
Section: Resultsmentioning
confidence: 99%
“…Much prior work has demonstrated that sum frequency intensities decrease with decreasing surface potentials either as a result of the decreasing surface field orienting interfacial liquid molecules less strongly, a decreasing χ (3) contribution to the sum frequency signal or both. McLoughlin et al have shown that adsorption of DNA to the cationic lipid DODAB (dioctadecyldimethylammonium bromide) leads to a decrease in surface potential of ≈0.3 V while adsorption of DNA to the zwitterionic lipid DSPC (distearoyl- sn -glycero-3-phosphocholine) in the presence of Ca 2+ (the change in surface potential for the bare DSPC monolayer in the presence of DNA was not measured) leads to a decrease in surface potential of less than 0.1 V. If we assume that DPTAP and diC14-amidine behave similarly to DODAB and DPPC similarly to DSPC, the change in spectral response with DNA adsorption appears to map qualitatively to the potential decrease: DNA adsorbed to a cationic lipid leads to a larger surface potential decrease than that adsorbed to a zwitterionic and the former system shows a larger decrease in hydrogen bonded OH stretch intensity than the latter.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the higherorder polarization and quantum correction should be further studied. [53][54][55]…”
Section: Time-dependent Representationmentioning
confidence: 99%
“… χ R ν ( 2 ) N normal a d s false⟨ β ν false⟩ The value of β ν increases when the frequency of the incoming IR pulse matches a vibrational transition of the adsorbate or interface leading to resonance enhancement of the SFG signal. As demonstrated by Eliel et al with a free electron laser and Richter et al with a tabletop solid state laser, IR fields that are broad in the frequency domain allow for collection of broadband SFG spectra within a single laser pulse, this approach can be utilized to monitor multiple vibrational modes during the adsorption/desorption process providing information about both the surface coverage and orientation of adsorbates. , Lastly, for the silica/aqueous interface the nonresonant contribution to the SFG signal has, on the molecular level, the same origins as the nonresonant SHG signal used in the χ (3) technique . Therefore, the nonresonant SFG signal can be modeled following the same theory described for the χ (3) technique in the previous section.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…51,[53][54][55][56][57][58][59] Lastly, for the silica/aqueous interface the nonresonant contribution to the SFG signal has, on the molecular level, the same origins as the nonresonant SHG signal used in the χ (3) technique. 60 Therefore, the nonresonant SFG signal can be modeled following the same theory described for the χ (3) technique in the previous section.…”
Section: Theoretical Backgroundmentioning
confidence: 99%